Perceived performances of peer learning and education approach on malaria prevention through primary schools communities in rural Ethiopia: Peer educators' perspectives - Deressa, Alemayehu; Eyeberu, Addis; Gamachu, Mulugeta; Debella, Adera; Abamecha Ababulgu, Fira (Frontiers in Public Health, 2022)
Abstract Background: Schools are viewed as a natural hub and an effective strategy for promoting community healthy practices such as malaria prevention and control measures. This study examined at the perceived performance of a peer learning and education approach to malaria prevention in rural primary school communities in Ethiopia, which had previously received little attention. Methods: A Post-intervention data were collected from 404 randomly selected peer educators from April 02 to Jun 08 2020 by using structured questionnaire. The Statistical Package for Social Sciences (SPSS) version 24.0 was used to analyze the data. Multiple linear regression was used to identify independent predictors of school-based peer learning and an education approach's perceived performance. A p-value of less than 0.05 was considered statistically significant. Results: Four hundred and one (99.2%) of the respondents completed the interview. The mean score of the perceived performance was 44.31(SD=6.13) which were above expected mean level with the range of 11-55. Feasibility (β= 0.253, 95% CI = [0.313, 0.682]), and appropriateness (β= 0.163, 95% CI = [0.099, 0.442]) were significantly associated with perceived performance. Self-efficacy, malaria risk perception, eagerness to share and learn from each other's experiences, and preference for more than one subject were all significantly associated with perceived performance, with (β= 0.097, CI = [0.017, 0.242]), (β= 0.143, CI = [0.071, 0.233]), (β= 0.207, CI = [0.308, 0.826]) and (β= 0.075, CI = [0.084, 2.511]) at 95% respectively. Conclusion: A notable high level of perceived performance of the peer learning and education approach to malaria prevention and control in schools. Thus, when designing and implementing such a program through schools, it is recommended to consider personal and social (team) factors such as self-efficacy, risk perceptions and peer education team spirits. Key words: peer learning, peer educators, malaria prevention, school, Ethiopia